(untitled) (CIPEEX, 2025)
Due to the high prevalence of fibrosarcoma, a neoplasm that affects connective tissue in dogs, it is imperative to explore alternative therapies that offer better results and reduce adverse effects. In this context, a liquid formulation of the photosensitizer methylene blue was developed and characterized. This formulation was then evaluated in the in vivo treatment of fibrosarcoma in dogs. To this end, a mixed-breed female dog was subjected to photodynamic therapy protocols. The results showed a significant reduction in the tumor, indicating that the therapy not only improved the clinical condition but also contributed to the dog’s well-being and quality of life.